PERBANDINGAN KASUS PERTANGGUNGJAWABAN PIDANA KORPORASI TERHADAP KECELAKAAN LALU LINTAS DI INDONESIA DAN AMERIKA SERIKAT: Comparative Analysis of Corporate Criminal Liability Cases for Traffic Accidents in Indonesia and the United States - Purba, Andika Temanta; Azwar, T. Keizerina Devi (Fakultas Hukum Universitas Komputer Indonesia, 2024)
Corporations are often overlooked in legal developments and participation in legal construction, making them vulnerable to access to justice. Corporations must obtain the same rights as humans in accordance with the legislation on corporations as legal subjects. This is to ensure fairness for those working within the company. The purpose of this research is to examine, discover facts, and analyze criminal liability for corporations regarding their vehicles involved in traffic accidents and to make a legal comparison between Indonesia and the United States. The method used is a type of normative juridical writing method using a case approach. Case examples were obtained from the Directory of Decisions of the District Courts in Indonesia and the Directory of Civil Courts in Dorchester County, South Carolina, United States. The research found that: The Traffic Law only focuses on the vehicle drivers; however, the reality is that some traffic accidents occur because companies do not conduct periodic testing on their vehicles. Periodic testing is the responsibility of the company to conduct testing periodically on its vehicles every 6 months, both used for public transportation and freight. However, based on the cases described: In Indonesia, traffic accidents caused by the company's negligence in periodic testing only focus on the driver's fault. Meanwhile, in the United States, the victim can file a lawsuit for damages in court, so the court decides that the company (Amazon) is fined USD 44.6 billion to the victim. Current traffic legislation in Indonesia is certainly not fully supportive of legal subjects; therefore, it is necessary to incorporate corporate criminal liability into the Traffic and Road Transportation Law in the future.